2017
DOI: 10.1016/j.jfda.2017.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Identification of cow milk in goat milk by nonlinear chemical fingerprint technique

Abstract: The objective of this paper was to develop a nonlinear chemical fingerprint technique for identifying and detecting adulteration of goat milk with cow milk. In this study, by taking the Belousov-Zhabotinsky oscillatory chemical reaction using acetone and substrates in goat milk or cow milk as main dissipative substances, when the same dosage of goat milk and cow milk was introduced to the "H + Mn + BrO + acetone" oscillating system respectively, nonlinear chemical fingerprints were obtained for goat milk and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…According to the aforementioned methods, nearinfrared reflectance spectroscopy (NIRS) and Raman spectroscopy have been reported that they are rapid and accurate methods for detecting melamine in milk powder, but they still need sample preparation and well-trained personnel. Therefore, it would be beneficial to develop simple and cost effective methods based on different principles from different aspects for distinguishing and evaluating samples, and the techniques may be complementary with each other (Ma et al, 2017b). Kinetic-catalytic reaction was one of the simple and rapid analytical methods compared to other methods (Gao et al, 2007).…”
Section: Study On the Influencing Factors Of Oscillation Chemical Rea...mentioning
confidence: 99%
See 2 more Smart Citations
“…According to the aforementioned methods, nearinfrared reflectance spectroscopy (NIRS) and Raman spectroscopy have been reported that they are rapid and accurate methods for detecting melamine in milk powder, but they still need sample preparation and well-trained personnel. Therefore, it would be beneficial to develop simple and cost effective methods based on different principles from different aspects for distinguishing and evaluating samples, and the techniques may be complementary with each other (Ma et al, 2017b). Kinetic-catalytic reaction was one of the simple and rapid analytical methods compared to other methods (Gao et al, 2007).…”
Section: Study On the Influencing Factors Of Oscillation Chemical Rea...mentioning
confidence: 99%
“…Kinetic-catalytic reaction was one of the simple and rapid analytical methods compared to other methods (Gao et al, 2007). Belousov-Zhabotinsky oscillatory chemical reaction (Belousov and Zhabotinsky were the names of the two Russian scientists, who were the first ones to study the reaction) was typical nonlinear chemical reaction system, which had made a great progress (Ma et al, 2017b), and many scholars had explained the mechanism of the reaction by different kinetic models. The most famous kinetic model was FKN (Field et al, 1972;Field & Schneider, 1989) model, and B-Z oscillatory reaction had been explained by this model.…”
Section: Study On the Influencing Factors Of Oscillation Chemical Rea...mentioning
confidence: 99%
See 1 more Smart Citation
“…The most common adulteration in dairy products is to use cow milk, which is cheaper, instead of milk of buffalo, goat, sheep or other dairy products that are advertised to be in the product (Ma et al 2017;Mabood et al 2017;Poonia et al 2017;Tsakali et al 2019). Thus correct labelling is essential to support fair trade practices (Guo et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The most common adulteration in dairy products is to use cow milk, which is cheaper, instead of milk of buffalo, goat, sheep or other dairy products that are advertised to be in the product (Ma et al . 2017; Mabood et al . 2017; Poonia et al .…”
Section: Introductionmentioning
confidence: 99%